Performance of Broilers Chicken Due to The Administration of Raw Propolis - Akhmad Endang Zainal Hasan; Ike Agustiani; Olive Wisepti Pratama; Syifa Khaerani; Mutholaah; Muhammad Zulkifli; Dimas Andrianto; Agus Setiyono (Indonesian Journal of Applied Research (IJAR), 2020)
The use of antibiotics as an Antimicrobial Growth Promoter (AGP) for livestock has been banned because antibiotic residues in livestock meat can trigger antibiotic resistance in consumers. Propolis is a natural source that has benefits like antioxidants, antiviral, antifungal, and antibiotic. The purpose of this study was to determine the effectiveness of the addition of feed from the optimal composition of raw propolis to increasing broiler chickens' body weight of broiler chickens. This study used broiler chickens as experimental animals. The chicken were grouped into six groups consisting of two control groups and four treatment groups with different level concentrations of propolis (2, 4, 6, and 8 g/kg feed). After treatment for four weeks, supplementation of raw propolis in the feed had not been able to provide a positive effect on growth performance and protein levels that were not significantly different from controls. Group chickens with propolis additions 6 g/kg feed showed the best results compared to other treatment groups. The group had final weight values, food conversion ratio (FCR), and carcass weight in 1970.67 gram, 1.52, and 1349.83 gram, respectively. The highest percentage of the carcass was shown by group chicken with propolis additions 2 g/kg feed, which is equal to 74.46%. Raw propolis can reduce feed consumption but increase feed conversion ratio.